Evaluation of combined efficacy of photodynamic therapy using indocyanine green photosensitizer and non-surgical periodontal therapy on clinical and microbial parameters in the management of chronic periodontitis subjects: A randomized split-mouth design - Sukumar, Kanchana; Tadepalli, Anupama; Parthasarathy, Harinath; Ponnaiyan, Deepa (Photodiagnosis and photodynamic therapy, 2020)
•In the current study, we have assessed the clinical and antimicrobial efficacy of multiple applications of photodynamic therapy (PDT) using indocyanine green (ICG) photosensitizer as an adjunct to conventional periodontal therapy at 3 and 6 months time period. At the end of the study period, statistically significant improvement was noted in clinical parameters among both the groups. Whereas, microbial analysis revealed significant greater reduction for all tested pathogens in test sites when compared to control sites (P ≤ 0.05). The outcome of the study suggests that adjunctive multiple PDT application along with non-surgical periodontal therapy may be beneficial in improving clinical and microbial parameters. The clinical efficacy of multiple applications of Photodynamic therapy (PDT) needs to be better investigated for the management of chronic periodontitis subjects. The aim of this study was to evaluate the clinical and antimicrobial efficacy of multiple application of PDT as an adjunct to scaling and root planning in management of moderate periodontal pockets. MATERIALS AND METHODS: 33 patients with bilateral periodontal destruction in mandibular posterior sextants were randomly treated with either test (SRP + multiplePDT) or control (SRP) intervention. PDT was employed with diode laser(810 nm) and Indocyanine green(ICG) dye at baseline, 1 st, 2nd and 4th week post SRP. Probing pocket depth (PPD), clinical attachment level (CAL), plaque index (PI), gingival index (GI), gingival bleeding index (GBI) were recorded at baseline, 3 and 6 months. Subgingival plaque samples were analysed for Porphyromonas gingivalis (P.g), Aggregatibacter actinomycetemcomitans (A.a), Tannerella forsythia (T.f), Fusobacterium nucleatum (F.n), Treponema denticola (T.d). Statistically significant improvement was noted in all clinical parameters in both the groups from baseline to 3 and 6 months. The mean PPD and CAL decreased in control sites from 5.83 ± 0.64 and 5.60 ± 0.72 at baseline to 3.80 ± 0.40 and 3.70 ± 0.91 at 6 months and in test sites from 5.93 ± 0.82 and 5.73 ± 0.69 to 3.40 ± 0.56 and 3.00 ± 0.91 at 6 months (P ≤ 0.05). Test sites showed significantly greater reduction in P.g, A.a, T.f, F.n and T.d compared to control sites at 3 and 6 months (P ≤ 0.05). The outcomes suggested that adjunctive multiple applications of PDT to SRP shows significant reduction in periodontal pathogens over SRP alone.